Kajian Keterampilan Metaphorical Thinking Siswa pada Materi Lingkaran - Mea Wiyana Selvani; Syaiful; Ilham Falani (Media Pendidikan Matematika, 2025)
This study aims to examine students’ metaphorical thinking skills in the topic of circles. Metaphorical thinking is a higher-order cognitive ability that enables students to relate abstract mathematical concepts to real-life experiences through six thinking stages: Connect, Relate, Explore, Analyze, Transform, and Experience (CREATE). This research employed a qualitative descriptive approach involving eleventh-grade students at SMA Negeri 2 Kota Jambi. Data were collected through observation, written tests on circle material, and semi-structured interviews. The results show that most students were able to connect circle concepts to real-life situations (Connect indicator) and identify relationships among circle elements (Relate indicator). However, some students still faced difficulties in the Explore and Analyze stages, which require deeper conceptual reasoning. The study concludes that metaphorical thinking skills play an essential role in helping students meaningfully and contextually understand circle concepts